2016
DOI: 10.1620/tjem.239.73
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Pentraxin 3 Levels in Diabetic Polyneuropathy Patients with Nociceptive Pain

Abstract: Diabetic polyneuropathy is the most common neurologic complication of diabetes mellitus. Underlying mechanisms of diabetic polyneuropathy are related to various metabolic and inflammatory pathways. Pentraxin 3 (PTX3) is an acute phase protein that is produced locally at the inflammatory sites by several cell types. Thioredoxin binding protein 2 (TBP2) is a thioredoxin regulator involved in intracellular energy pathways and cell growth. We measured the plasma levels of PTX3 and TBP2 in type 2 diabetic patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…Our study are in agreement with [9] who, showed that serum pentraxin-3 was significantly higher in diabetic patients compared to controls Yuichi et al,2018 also found that serum PTX3 level was significantly positively correlated with existence of diabetes, HbA1c (r = 0.379, P<0.001; r = 0.431, P<0.001).…”
Section: Discussionsupporting
confidence: 93%
“…Our study are in agreement with [9] who, showed that serum pentraxin-3 was significantly higher in diabetic patients compared to controls Yuichi et al,2018 also found that serum PTX3 level was significantly positively correlated with existence of diabetes, HbA1c (r = 0.379, P<0.001; r = 0.431, P<0.001).…”
Section: Discussionsupporting
confidence: 93%
“…But at the same time it has been shown that diabetic vascular complications apart from DR also affect the serum levels of PTX3 protein. [38][39][40] Another limitation of our study was its relatively small sample size. It was because of PTX3 levels might be affected by several systemic diseases such as cardiovascular or cerebrovascular diseases, chronic kidney and liver failure, autoimmune disorders, irregular systemic hypertension.…”
Section: Eyementioning
confidence: 97%
“…Type 2 diabetes mellitus is a disorder characterized by progressive loss of pancreatic beta cell function and resistance to the effects of insulin in organs such as muscle, fat and liver (Ferranini, 1998). Chronic systemic inflammation is the main reason of vascular complications in DM (Salcini et al, 2016). Berberine has been used for the adjuvant treatment of type 2 diabetes mellitus, hyperlipidemia, and hypertension (Lan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%